2018
DOI: 10.3390/w10040469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Junction Angle on Turbulent Flow at a Hydraulic Confluence

Abstract: Despite the existing knowledge concerning the hydrodynamic processes at river junctions, there is still a lack of information regarding the particular case of low width and discharge ratios, which are the typical conditions of mountain river confluences. Aiming at filling this gap, laboratory and numerical experiments were conducted, comparing the results with literature findings. Ten different confluences from 45 • to 90 • were simulated to study the effects of the junction angle on the flow structure, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 38 publications
4
12
0
2
Order By: Relevance
“…This fact is ascribed to the acceleration induced by the lateral flow that approaches the post-confluence channel. Furthermore, it is also evidenced that the higher the θ, the more extended the retardation zone and the lower the velocities in this region [95].…”
Section: Confluence Planformmentioning
confidence: 86%
See 1 more Smart Citation
“…This fact is ascribed to the acceleration induced by the lateral flow that approaches the post-confluence channel. Furthermore, it is also evidenced that the higher the θ, the more extended the retardation zone and the lower the velocities in this region [95].…”
Section: Confluence Planformmentioning
confidence: 86%
“…Ashmore and Parker [78] described this effect as a decrease in curvature radius, where a higher θ causes the flows of the two tributaries to pass through with enhanced turbulence. Penna et al found that the maximum streamwise flow velocity does not necessarily increase with the θ, and it does not always occur in the contraction zone [95]. This fact is ascribed to the acceleration induced by the lateral flow that approaches the post-confluence channel.…”
Section: Confluence Planformmentioning
confidence: 99%
“…Nadia el al. [14], with their experimental work, found that the higher the junction angle, the wider and longer the retardation zone at the upstream junction corner and the separation zone, and the greater the flow deflection at the entrance of the tributary into the post-confluence channel.…”
Section: Introductionmentioning
confidence: 88%
“…Although many studies on junction angles have been done up until now (Best and Rhoads, 2008;Santos and Stevaux, 2017), knowledge about its formation and determination still maintains strong interest (Hooshyar et al, 2017;Alomari et al, 2018;Yukawa et al, 2019). However, the majority of the studies in this topic is directed to the understanding of the flow regime, of the interactions that occur inside the channel, and of the sediment mobility of the channels (Park and Latrubesse, 2015;Penna et al, 2018;Herrero et al, 2018;Dixon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%